2004
DOI: 10.1023/b:jarg.0000046204.81682.67
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Elevation in Obese Women with PCOS: A Continuing Controversy

Abstract: Purpose : To evaluate leptin levels in a sample of obese women with PCOS and compare the results with obese and non-obese control, to be ultimately correlated with BMI, and insulin sensitivity. Methods : Leptin and insulin assays by immuno-radiometric method, glucose assay by enzymatic colorimetric method. Results : Leptin levels were significantly different between obese and non-obese subjects, and were significantly different between insulin resistant and non-insulin resistant obese PCOS, but were not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
3
4
2
1
Order By: Relevance
“…We found significantly higher leptin levels when BMI and waist circumference increased in both patients and controls and in accordance with previous studies, close relations were demonstrated between leptin and measures of fat mass and insulin sensitivity (8,(42)(43)(44)(45)(46)(47). Our findings of insignificant associations between leptin and androgen levels are in agreement with previous studies (42,(44)(45)(46).…”
Section: Whr Adjustedsupporting
confidence: 93%
See 1 more Smart Citation
“…We found significantly higher leptin levels when BMI and waist circumference increased in both patients and controls and in accordance with previous studies, close relations were demonstrated between leptin and measures of fat mass and insulin sensitivity (8,(42)(43)(44)(45)(46)(47). Our findings of insignificant associations between leptin and androgen levels are in agreement with previous studies (42,(44)(45)(46).…”
Section: Whr Adjustedsupporting
confidence: 93%
“…Our findings of insignificant associations between leptin and androgen levels are in agreement with previous studies (42,(44)(45)(46). Further supporting a minor relation between testosterone and leptin, Krotkiewski et al (48) found no significant changes of leptin levels during anti-androgen treatment in PCOS.…”
Section: Whr Adjustedsupporting
confidence: 93%
“…In contrast to adiponectin, elevated leptin levels are implicated in the pathogenesis of obesity and associated with insulin resistance (41). Recent studies have linked leptin levels to the degree of adiposity and insulin resistance in obese PCOS and control subjects (42,43). We did not find a significant difference in serum adiponectin and leptin levels in the two groups.…”
Section: Discussioncontrasting
confidence: 73%
“…26 In this study, the leptin levels in controls and PCOS cases seemed to be much higher than those reported in different populations, including the United States, 27 Turkey, 28 and Egypt. 29 Leptin, as expected, was correlated with BMI in both controls and PCOS cases, confirming that leptin is an appropriate marker of obesity. 30 In addition, results from the present study suggest that age is positively correlated with age in PCOS cases.…”
supporting
confidence: 78%